Metachronous neoplasms in patients with laterally spreading tumours during surveillance. Issue 3 (18th February 2021) - Bogie, Roel M. M.; Winkens, Bjorn; Retra, Sean J. J.; le Clercq, Chantal M. C.; Bouwens, Mariëlle W.; Rondagh, Eveline J. A.; Chang, Li‐Chun; de Ridder, Rogier; Hoge, Chantal; Straathof, Jan‐Willem; Goudkade, Danny; Sanduleanu‐Dascalescu, Silvia; et al.
Abstract: Background: Laterally spreading tumours represent a major challenge for endoscopic detection and resection. Objective: To examine synchronous and metachronous neoplasms in patients with laterally spreading tumours. Methods: We prospectively collected colonoscopy and histopathology data from patients who underwent colonoscopy in our centre at up to 6 years' follow‐up. Post‐resection surveillance outcomes between laterally spreading tumours, flat colorectal neoplasms 10 mm or greater, and large polypoid colorectal neoplasms, polypoid colorectal neoplasms 10 mm or greater, were compared. Results: Between 2008 and 2012, 8120 patients underwent colonoscopy for symptoms (84.6%), screening (6.7%) or surveillance (8.7%). At baseline, 151 patients had adenomatous laterally spreading tumours and 566 patients had adenomatous large polypoid colorectal neoplasms. Laterally spreading tumour patients had more synchronous colorectal neoplasms than large polypoid colorectal neoplasm patients (mean 3.34 vs. 2.34, p  < 0.001). Laterally spreading tumour patients significantly more often developed metachronous colorectal neoplasms (71.6% vs. 54.2%, p = 0.0498) and colorectal neoplasms with high grade dysplasia/submucosal invasion than large polypoid colorectal neoplasm patients (36.4% vs. 15.8%, p  < 0.001). After correction for age and gender, laterally spreading tumour patients were more likely than large polypoid colorectal neoplasm patients to develop a colorectal neoplasm with high grade dysplasia or submucosal invasion (hazard ratio 2.9, 95% confidence interval 1.8–4.6). The risk of metachronous colorectal cancer was not significantly different in laterally spreading tumours compared to large polypoid colorectal neoplasm patients. Conclusion: Patients with laterally spreading tumours developed more metachronous colorectal neoplasms with high grade dysplasia/submucosal invasion than large polypoid colorectal neoplasm patients. Based on these findings endoscopic treatment and surveillance recommendations for patients with laterally spreading tumours should be optimised. Key Summary: Summarize the established knowledge on this subject Laterally spreading tumours (LSTs) are a heterogeneous group of large, predominantly benign flat neoplasms that can be endoscopically treated, requiring additional time and expertise LSTs consist of different endoscopic subtypes which are predictive of the risk of submucosal invasion (SMI) Patients with LSTs harbour more synchronous neoplasms than patients with large polypoid colorectal neoplasms (LP‐CRNs) What are the significant and/or new findings of this study? Patients with LSTs more frequently have metachronous neoplasms than patients with LP‐CRNs, justifying strict surveillance LSTs can be effectively managed by conventional endoscopic resections in most cases